The Jung-Kirsch letters : the correspondence of C.G. Jung and James Kirsch - Jung, C. G.; Lammers, Ann Conrad (London : Routledge, 2016)
This book charts Jung's 33-year correspondence with James Kirsch, adding depth and complexity to the previously published record of the early Jungian movement.
Includes bibliographical references (pages 322-335) and index.
Keywords: Psychoanalysts -- Correspondence; Psychiatrists -- Correspondence